Surgical treatment of trapezius palsy: A systematic review. (June 2020) - Elsawi, Rawaan S; Vancolen, Seline Y; Horner, Nolan S; Khan, Moin; Alolabi, Bashar
Background: Trapezius palsy results from injury to the spinal accessory nerve. The condition presents with loss of shoulder abduction, pain, and winging of the scapula. Surgical treatment may improve functional outcomes and quality of life. Purpose: The purpose of this study was to report and evaluate the clinical outcomes following surgical management of trapezius palsy. Study design: Systematic review. Methods: The electronic databases EMBASE, MEDLINE, and PubMed were searched for studies and relevant data were abstracted. Only studies reporting on outcomes after the surgical treatments of trapezius palsy were included. Results: A total of 10 studies including 192 patients were included in this review. All surgical interventions resulted in improved function and pain reduction. Patients reported high satisfaction (90–92%) following nerve reconstruction or the Eden–Lange procedure, in comparison to neurolysis. The most common procedure reported was the Eden–Lange muscle transfer (32% reported cases) demonstrating the highest patient satisfaction rates with low complication rate of 7.7%. Conclusion: Patients failing conservative treatment report good outcomes following surgical treatment of trapezius palsy. All reported surgical procedures demonstrate reduction in pain the best results from the Eden–Lange muscle transfer. Further high-quality comparative studies are required to make definitive conclusions regarding the comparative efficacy of each surgical procedure.